(untitled) (Baghdad Science Journal, 2021)
In the present study, the growth and total lipid contents of two oleaginous fungal isolates Aspergillus terreus, Aspergillus fumigatus were compared in different nitrogen and organic carbon sources. Artificially the fungi were cultured on media consisting of various mono- or di- or polysaccharides and peptone or yeast extract as elementary sources for carbon and nitrogen, respectively. Media containing sucrose /yeast extract or glucose/ yeast extract were the most effective for lipid production from fungal, during two weeks incubation period, the highest biomass of dry weight was (19.6 , 18.8) g / L , (25.8 , 30.5) g /L and lipid yield (1, 0.97 )g/L, (0.65, 0.65) g/ L for two isolates Aspergillus terreus and Aspergillus fumigatus respectively then followed maltose/ yeast extract then starch / yeast extract .Analysis of fatty acid produced by two fungal isolates using Gas Chromatography showed the existence of a wide range of fatty acids, these fatty acids were together saturated and unsaturated. The results revealed that the unevenness in the fatty acids composition mainly depends on the type of carbon and nitrogen sources. The existence of saturated and mono saturated fatty acids in A.fumigatus, A. terreus prove that they are good candidate for biodiesel production. The analysis of fatty acid from the fungal growth showed the existence of a wide range of fatty acids Palmitic ,Oleic acids , stearic acid and linoleic acid together saturated and unsaturated. The results revealed that the unevenness in the fatty acid composition mainly depends on the type of carbon and nitrogen sources. The presence of saturated and mono saturated fatty acid in A.fumigatus , A. terreus prove that it is a good candidate for biodiesel production.